The status of e-learning, personality traits, and coping styles among medical students during the COVID-19 pandemic: a cross-sectional study - Wei, Junfan; Yun, Zhengcheng; Zhang, Yang; Mei, Xiaoxiao; Ba, Li; Peng, Huan; Li, Na; Li, Meng; Liu, Zhu; Liu, Hanjiao (Frontiers in Psychiatry, 2023)
Abstract：[Objective] The objective of this study was to explore the learning preferences and habits of medical students during the pandemic home-based e-learning, and to investigate the incidence of adverse emotions, optimistic character level and coping style. To explore the influencing factors of adverse emotions. [Methods] A cross-sectional survey was conducted in China from March to June 2022. Medical students were recruited from three universities in China, and a questionnaire survey was conducted. The questionnaires consisted of a ‘e-learning preferences and habits questionnaire’, life orientation test questionnaire (LOT-R), and simple coping style questionnaire (SCSQ). Finally, a total of 492 medical students who met the inclusion and exclusion criteria became the research subjects and completed the survey. [Results] 57.7% believed they experienced no adverse emotions during home e-learning. ①During the COVID-19 pandemic, the score of optimistic personality of medical students was （7.25±1.933）, and the score of pessimistic personality was （5.82±2.240）. The score of positive coping was （21.75±5.379）, and the score of negative coping was （11.75±3.611）. ②The occurrence of medical students' adverse emotions during e-learning was influenced by “Whether there is a private, quiet space to study”, “Degree of knowledge mastery”, “Physical discomfort or not”, “Keep a regular schedule or not”, “Optimistic personality tendency”. [Conclusion] This study demonstrates the during home e-learning , most medical students have their own learning equipment and can meet their learning needs. Their favorite mobile device to use is a mobile phone, and their favorite method of teaching is to provide course playback. More than half of medical students believe that they have some inconvenience in conducting research during home e-learning. With regard to teacher's real-time screen, the largest number of medical students support teachers turning on live screens so that they feel like they are interacting with the teacher. The preference for blended teaching is highest among medical students. Based on the statistic analysis, the factors that “Whether there is a private, quiet space to study”, "Degree of knowledge mastery", "Physical discomfort or not", "Keep a regular schedule or not", and "Optimistic personality tendency" may be the influencing factors for the occurrence of adverse emotions.